The Arabidopsis thaliana mitogen‐activated protein kinases MPK3 and MPK6 target a subclass of 'VQ‐motif'‐containing proteins to regulate immune responses. Issue 2 (22nd April 2014) - Pecher, Pascal; Eschen‐Lippold, Lennart; Herklotz, Siska; Kuhle, Katja; Naumann, Kai; Bethke, Gerit; Uhrig, Joachim; Weyhe, Martin; Scheel, Dierk; Lee, Justin
Summary: Mitogen‐activated protein kinase (MAPK) cascades play key roles in plant immune signalling, and elucidating their regulatory functions requires the identification of the pathway‐specific substrates. We used yeast two‐hybrid interaction screens, in vitro kinase assays and mass spectrometry‐based phosphosite mapping to study a family of MAPK substrates. Site‐directed mutagenesis and promoter‐reporter fusion studies were performed to evaluate the impact of substrate phosphorylation on downstream signalling. A subset of the Arabidopsis thaliana VQ‐motif‐containing proteins (VQPs) were phosphorylated by the MAPKs MPK3 and MPK6, and renamed MPK3/6‐targeted VQPs (MVQs). When plant protoplasts (expressing these MVQs) were treated with the flagellin‐derived peptide flg22, several MVQs were destabilized in vivo . The MVQs interact with specific WRKY transcription factors. Detailed analysis of a representative member of the MVQ subset, MVQ1, indicated a negative role in WRKY‐mediated defence gene expression – with mutation of the VQ‐motif abrogating WRKY binding and causing mis‐regulation of defence gene expression. We postulate the existence of a variety of WRKY‐VQP‐containing transcriptional regulatory protein complexes that depend on spatio‐temporal VQP and WRKY expression patterns. Defence gene transcription can be modulated by changing the composition of these complexes – in part – through MAPK‐mediated VQP degradation.